Interference between different serodemes of Trypanosoma congolense in the establishment of superinfections in goats following transmission by tsetse - Dwinger, R.H.; Luckins, G.; Murray, M.; Rae, P.; Moloo, S.K. (Wiley, 1986)
Summary When domestic ruminants cyclically infected with Trypanosoma congolense are superinfected with a different serodeme of the same species, an interference phenomenon occurs which delays the development of the second cyclical infection. Experiments were carried out to investigate the influence of the time interval between the two infections on the degree of interference and to follow the course of the superinfection clinically, serologically and histologically. Goats infected with tsetse‐transmitted T. congolense IL 1587 were either infected simultaneously or 7, 14, 18, 28 or 35 days later with a different serodeme, T. congolense IL 1180. Skin reactions due to superinfection were either absent or smaller in size and delayed in onset compared with control animals undergoing a primary infection with T. congolense IL 1180 which had been initiated by tsetse fly bites. All animals were treated with the trypanocidal drug Berenil 21 days after superinfection and 3 weeks later challenged with T. congolense IL 1180 using tsetse flies. The goats that had been infected simultaneously with the two serodemes were immune to the homologous challenge, but 11 (85%) of the animals that had been superinfected were not. The effect of interference on the host immune response to T. congolense IL 1180 was most marked in animals superinfected at day 7; thereafter there was evidence that the ability to respond immunologically against secondary infection was gradually recovered. Histological examination of skin removed 7 days after a simultaneous infection of goats with two serodemes, showed trypanosomes and a cellular reaction similar to that following infection with a single serodeme. In skin removed 7 days after superinfection of goats that had been infected for 7 days, the cellular response was less pronounced and trypanosomes were not seen, although by 14 to 16 days numerous trypanosomes were present and there was a marked cellular infiltrate. It is postulated that the presence or absence of a factor induced shortly after initiation of a trypanosome infection in the skin of goats might delay parasite development when metacyclic trypanosomes are deposited by tsetse following superinfection.